Marshall cavendish cambridge primary maths pupil's book 6 - Po, Huat Seng; Soon, Spario (Marshall Cavendish Education Singapore, 2017)
Mathematics. 6, book Marshall Cavendish is a supplementary resource for Grade 5 students that offers hands-on practice through engaging activities. It complements the main textbook by providing additional exercises that reinforce key mathematical concepts such as fractions, decimals, geometry, and problem-solving. The activity book encourages active participation, allowing students to apply what they've learned in the classroom through puzzles, word problems, and interactive tasks. The structure promotes independent learning, critical thinking, and skill mastery, making it an essential tool for enhancing math proficiency at this level.